Solid oxide fuel cell reactor analysis and optimisation through a novel multi-scale modelling strategy - Amiri, Amirpiran; Vijay, P.; Tadé, M.; Ahmed, K.; Ingram, Gordon; Pareek, V.; Utikar, Ranjeet (Elsevier Ltd, 2015)
The simulation of a solid oxide fuel cell (SOFC) that incorporates a detailed user-developed model was performed within the commercial flowsheet simulator Aspen Plus. It allows modification of the SOFC's governing equations, as well as the configuration of the cell's fuel-air flow pattern at the flowsheet level. Initially, the dynamic behaviour of single compartment of a cell was examined with a 0D model, which became the building block for more complex SOFC configurations. Secondly, a sensitivity analysis was performed at the channel (1D) scale for different flow patterns. Thirdly, the effect of fuel and air flow rates on the predominant distributed variables of a cell was tested on a 2D assembly. Finally, an optimisation study was carried out on the 2D cell, leading to a robust, optimal air distribution profile that minimises the internal temperature gradient. This work forms the foundation of future stack and system scale studies.